أثر السياسات النقدية والمالية على تقلبات أسعار الأسهم في تركيا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت الدراسة لاختبار أثر أدوات السياستين النقدية والمالية على أسعار الأسهم في السوق المالية التركية، وذلك باستخدام العرض النقدي وأسعار الفائدة كمتغيرات عن السياسة النقدية، والإنفاق الحكومي والإيرادات الضريبية، كمتغيرات عن السياسة المالية، ومؤشر أسعار الأسهم في سوق اسطنبول المالي (Bist100) كمتغير عن سوق المال، وذلك باستخدام بيانات شهرية للفترة بين عامي (2006-2016). وبإجراء تحليل انحدار باستخدام طريقة المربعات الصغرى (OLS)، خلصت الدراسة إلى أن أدوات السياسة النقدية والمتمثلة بالعرض النقدي وأسعار الفائدة، ترتبط بعلاقة عكسية مع أسعار الأسهم في السوق المالية التركية. وبإجراء اختبار (VECM) لتحديد فيما إذا كان هنالك علاقة في الأجلين الطويل والقصير بين المتغيرات المدروسة، تبين أن تغيرات أسعار الفائدة لها علاقة مع تقلبات أسعار الأسهم في الأجلين القصير والطويل، بينما تغيرات العرض النقدي لها علاقة في الأجل الطويل فقط. كما توصلت الدراسة إلى أنه لا توجد علاقة بين أدوات السياسة المالية، المتمثلة بالإنفاق الحكومي والإيرادات الضريبية، والتقلبات في أسعار الأسهم في السوق المالية التركية. The study aims to examine the effect of fiscal and monetary policies tools, on the price of stocks in Turkish financial market, by using money supply, and interest rate as a variables for monetary policy, government expenditures, and tax revenues as a variables for fiscal policy, and the Istanbul price index (Bist100) as a variable for financial market, using monthly data for the period (2006-2016). Moreover, by applying a liner regression using the ordinary least square (OLS), the study concluded that the monetary policy embodied in money supply and interest rate, have a reverse relation with stock prices in the Turkish financial market. Also by using (VECM) test to determen if there any relation in the long and short run between tested variables, it was found that the interest rate have a relation with volatility of stock prices, in the long run and short run, while money supply has relationship in the long run only. The study also finds that there is no relationship between fiscal policy tools, embodied in government expenditure and tax revenues, and the volatility of stock prices in financial market of Turkey.